The effect of the Keys to Knowledge strategy on the acquisition of chemical concepts among second-year intermediate students (Journal of the College of Basic Education, 2024)
This research aims to identify the effect of the Knowledge Keys strategy on the acquisition of chemical concepts among second-year intermediate students. The following null hypothesis was derived: “There is no statistically significant difference at the level of significance (0.05) between the average scores of the experimental group students who will study the chemistry subject according to the Keys to Knowledge strategy and the average scores of the control group students who will study the same subject in the normal way in the test for acquiring chemical concepts.” ".An experimental design with two experimental and control groups with a post-test was chosen to acquire chemical concepts. To achieve the goal of the research, a purposive sample consisting of (86) students was chosen and distributed among the two research groups. The number of students in the experimental group was (44) students and the number of students in the control group was (42) students. Equivalence was conducted between the students of the two research groups with the following variables.To achieve the goal of the research, the researcher prepared the research tool, a test for the acquisition of chemical concepts: consisting of (60) objective items with four alternatives. Its apparent validity was extracted by presenting it to a group of arbitrators in education and science teaching methods. The content validity was also extracted in light of the test’s conformity. For the content studied, the power of distinction, the difficulty factor, and the effectiveness of incorrect alternatives were calculated for each item of the test using appropriate statistical methods, and reliability was extracted using the split-half method, so it reached (0.77) before correction and (0.87) after correction.After analyzing the results statistically using a t-test for two independent samples, the results resulted in the superiority of the experimental group that studied using the Keys to Knowledge strategy over the control group that studied in the usual way in testing the acquisition of chemical concepts. In light of the research results, the researcher developed A number of recommendations and proposals were mentioned in Chapter Four.